Risk Perception and PTSD Symptoms of Medical Staff Combating Against COVID-19: A PLS Structural Equation Model - Yin, Qianlan; Chen, Aibin; Song, Xiangrui; Deng, Guanghui; Dong, Wei (Frontiers in Psychiatry, 2021)
Medical staff were battling against COVID-19 at the expense of their physical and mental health, particularly at risk for post-traumatic stress disorder (PTSD). In this case, intervening PTSD of medical staff and preparing them for future outbreaks are important. Previous studies showed that perceived stress was related to the development of PTSD. Hence, in this study, the association between risk perception of medical staff and PTSD symptoms in COVID-19 and the potential links were explored. 304 medical staff’s exposure to COVID-19 patients, risk perception for working during COVID-19, PTSD symptoms, anxiety, and sleep quality were measured. Mediation analysis tested the indirect effects of anxiety and sleep quality on the relationship between risk perceptions and PTSD symptoms. 27.6% of participants were deemed as having probable PTSD diagnosis. Mediation analysis showed a significant chain mediating effect of anxiety and sleep quality on the relationships between risk perceptions and PTSD symptoms; higher risk perceptions were related to increased anxiety, worsened sleep quality, and severe PTSD symptoms. Conclusively, medical staff have a high prevalence of PTSD symptoms after 3 months of COVID-19. Their PTSD symptoms were associated with the perceived risk level through the potential links with anxiety and sleep quality. Therefore, risk perception could be critical for our medical staff's responses to public health emergencies. it could be plausible to intervene in the perceived stress to alleviate aroused anxiety and improve sleep quality, thereby deter the development of PTSD.